Isolation and Characterization of Defensins Genes from Vietnamese Brassica juncea - Thuong, Vo Thi Hoai; Anh, Tran Thi Thuy; Van, Nguyen Thi Hong (VNU Journal of Science: Natural Sciences and Technology, 2016)
Abstract: Plant defensins are small, basic cysteine-rich peptides ranging from 45 to 54 amino acids and are positively charged. They are a part of the innate immune system and possess antifungal and/or antibacterial activities found in many plant species, including Brassica family. Brassica juncea has been known as a nutritional vegetable, medicinal plant species and an oilseed crop in many countries. It has also been reported to be heat- and drought-tolerant and resistant to fungal diseases. This study aimed to isolate and characterize the BjAFP defensins genes from Vietnamese B. juncea . As the result, three nucleotide sequences of defensins genes were amplified, including BjAFP1 , BjAFP4 -like and an unpublished gene called BjAFPx . By comparison of DNA sequences from PCR and RT-PCR products, the result showed that, each gene consisted of one intron and two exons. Two exons had respectively 64 nucleotides and 179 nucleotides while intron contains 91 nucleotides in BjAFP1 , 93 nucleotides in BjAFP4 and 98 nucleotides in BjAFPx . Besides, gene BjAFP1 expressed at transcription level in all tissues: stem, root, leaf, flower and seed of B. juncea . In comparison of the nucleotide sequence of BjAFP1 with two published sequences of this gene in Genbank, the single nucleotide polymorphisms in BjAFP1 have been identified, including one missense substitution at position 54 in nucleotide sequence, which replcaed amino acid phenylalanine by leucine, and three synonymous at positions 51, 204 and 225 in nucleotide sequence. Keywords: Brassica juncea, defensin, BjAFP1, BjAFP4, BjAFPx.